A New Paradigm of Common Link Theory in Contemporary Hadith Studies - Wahid, Abdul Hakim; Rasyid, Harun (Millati: Journal of Islamic Studies and Humanities, 2024)
This article aims to explore the theory of common links in contemporary hadith research which was used differently from the beginning of its invention by Joseph Schacht and developed by Juynboll, who focuses only on discovering the originator or person in charge of the dissemination of a hadith. By using qualitative research with a historical approach, this article concludes that in the current context, the common link theory can be used to strengthen the authenticity of the prophet’s hadith because by using the source of the entire hadith book, a person with a common link status will be signed to a companion and even the prophet himself. Given the analysis that has been provided, it is clear that hadith scholars who are Muslim and non-Muslim have taken a keen interest in and debated Joseph Schacht’s common link thesis, which Juynboll further expanded. Individual religious beliefs significantly influence the implementation and acceptance of the theory, resulting in differing degrees of support and criticism. There is no denying the common connection phenomena among isnad systems, even if many Muslim academics have widely rejected it. This research indicates that the common link theory can be used to support the veracity of particular hadiths, in contrast to some objections. Its potential utility in hadith validation is highlighted by the research, which finds cases in which the common link is attributed to the Prophet Muhammad (SAW) and his associates.